Ribosomally-synthesised cyclic peptides from plants as drug leads and pharmaceutical scaffolds. Issue 10 (1st June 2018) - Craik, David J.; Lee, Meng-Han; Rehm, Fabian B.H.; Tombling, Benjamin; Doffek, Benjamin; Peacock, Hayden
Graphical abstract: Abstract: Owing to their exceptional stability and favourable pharmacokinetic properties, plant-derived cyclic peptides have recently attracted significant attention in the field of peptide-based drug design. This article describes the three major classes of ribosomally-synthesised plant peptides – the cyclotides, the PawS-derived peptides and the orbitides – and reviews their applications as leads or scaffolds in drug design. These ribosomally-produced peptides have a range of biological activities, including anti-HIV, cytotoxic and immunomodulatory activity. In addition, recent interest has focused on their use as scaffolds to stabilise bioactive peptide sequences, thereby enhancing their biopharmaceutical properties. There are now more than 30 published papers on such 'grafting' applications, most of which have been reported only in the last few years, and several such studies have reported in vivo activity of orally delivered cyclic peptides. In this article, we describe approaches to the synthesis of cyclic peptides and their pharmaceutically-grafted derivatives as well as outlining their biosynthetic routes. Finally, we describe possible bioproduction routes for pharmaceutically active cyclic peptides, involving plants and plant suspension cultures.